DEPOLIMERISASI PET PASCA KONSUMSI MELALUI GLIKOLISIS DENGAN KATALIS - Rahmayanti, Ardhana (Universitas Nahdlatul Ulama Sidoarjo, 2015)
Polyethylene terephthalate (PET) is a polyester which is widely used as a container or packaging material, especially mineral water and soft drinks. Recycling is necessary to overcome the post-consumer PET waste PET difficult because degraded naturally. Chemical recycling is an appropriate method for depolymerisation. Glycolysis is the method that is often used as the process was easy. Optimization parameters of glycolysis on the rate of reaction in the efforts to improve the products of glycolysis has been done as the use of catalysts. Metal acetate catalysts such as zinc acetate is a catalyst which shows good activity in the reactions of glycolysis, but the catalyst is non-biodegradable and toxic. The metal oxide catalysts are also many well developed but these catalysts are toxic, corrosive and can cause severe pollution. More environmentally friendly catalysts such as sodium salt today began much developed to minimize the impact to the environment.